Characterization of a hybrid pixel counting detector using a silicon sensor and the IBEX readout ASIC for electron detection. (28th October 2021) - Fernandez-Perez, S.; Boccone, V.; Broennimann, C.; Disch, C.; Piazza, L.; Radicci, V.; Rissi, M.; Schulze-Briese, C.; Trueb, P.; Zambon, P.
Abstract: In this paper we report on the performance of a Hybrid Pixel Detector — consisting on an IBEX ASIC bump-bonded to a 450 μm-thick Silicon sensor with a pixel size of 75 μm — used as a direct electron detector up to 300 keV. The count homogeneity was found to have a dispersion below 1%. Energy spectra were recorded for electron energies in the range 20–80 keV, showing a significant full-peak energy loss due to the entrance contact dead layer only for impinging electrons below 30 keV. MTF and DQE were measured at 100 keV and 200 keV in low-flux regime for several threshold energies. Zero-frequency DQE values are up to 0.85 and 0.9 for the two electron energies, respectively, while for increasing frequencies the DQE fall more rapidly for the 200 keV case as a consequence of the higher degradation in spatial resolution. Based on the analysis of the cluster distribution of single-events we were also able to estimate the DQE(0) at 300 keV, which is close to unity for low thresholds. The system response linearity was tested at 80 keV in both paralyzable and non-paralyzable counting mode, yielding a 10% count loss at 0.8 Mcts/s/pix and 1.7 Mcts/s/pix, respectively, and a 50% count loss at 7 Mcts/s/pix and 16 Mcts/s/pix, respectively. FLUKA-based Monte Carlo simulations were used to cross-validate the experimental results and to gain a better understanding of the underlying physical processes.